1998
DOI: 10.1093/jnci/90.17.1284
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Altered Patterns of p27KIP1 Gene Expression in Benign Prostatic Hyperplasia and Prostatic Carcinoma

Abstract: On the basis of these results, we infer that loss of p27Kip1 expression in the human prostate may be causally linked to BPH and that BPH is not a precursor to prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
149
3
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(162 citation statements)
references
References 43 publications
8
149
3
2
Order By: Relevance
“…Alterations of p27 gene expression have been found in BPH and prostatic carcinoma. 44 In this study, we found that exogenous IGF-1 decreased the p27 protein level in BPH-1 cells. Similarly, intracellular p27 protein levels of BPH-1 cells decreased significantly when co-cultured with c-jun ϩ/ϩ fibroblasts, particularly after 24 hours of co-culture (Figure 6C).…”
Section: Igf-1 and Stromally Expressed C-jun Regulate Cyclin D Levelsmentioning
confidence: 50%
“…Alterations of p27 gene expression have been found in BPH and prostatic carcinoma. 44 In this study, we found that exogenous IGF-1 decreased the p27 protein level in BPH-1 cells. Similarly, intracellular p27 protein levels of BPH-1 cells decreased significantly when co-cultured with c-jun ϩ/ϩ fibroblasts, particularly after 24 hours of co-culture (Figure 6C).…”
Section: Igf-1 and Stromally Expressed C-jun Regulate Cyclin D Levelsmentioning
confidence: 50%
“…16 Kyprianou's group has shown loss of p27 in prostatic carcinoma as well as the important observation that this loss is associated with higher proliferative activity and higher tumor grade. 17 Cordon-Cardo et al 18 have demonstrated loss of p27 in prostatic carcinoma, as well as diffuse p27 staining in normal prostate epithelium and a distinct absence of staining in BPH nodules.…”
Section: Discussionmentioning
confidence: 97%
“…20 While approximately one-third of our patients showed decreased staining for p27 in hyperplasia, the effect was more prominent in defined nodules (43%), which is consistent with the findings of other investigators. 18 The process of apoptosis protects the integrity of the genome by eliminating cells with extensive DNA damage or those undergoing uncontrolled proliferation. 11 For instance, during development, RB knockout mice did not experience uncontrolled cellular growth as expected because apoptotic processes eliminated abnormally cycling cells.…”
Section: Discussionmentioning
confidence: 99%
“…The p27 Kip1 protein expression is decreased in a number of tumor types, including breast, colon, prostate and ovarian tumors (Catzevalos et al, 1997;Ciaparrone et al, 1998;Cordon-Cardo et al, 1998;Masciullo et al, 1999). Conversely in BRCA1 knockout mouse models, reduction of BRCA1 is accompanied by an increase in the expression of p27 Kip1 at the mRNA and protein levels (Brodie et al, 2001;Deans et al, 2004).…”
Section: Discussionmentioning
confidence: 99%